RANCANG BANGUN PERALATAN PENGUSIR HAMA TIKUS DENGAN SISTEM KOMUNIKASI BERBASIS LoRA: Bahasa Indonesia - Arena, Ghinnata Alsyah; Wisaksono, Arief; Sulistyowati, Indah; Ahfas, Akhmad (Jurnal Al Ulum LPPM Universitas Al Washliyah Medan, 2025)
Pests plague farmers both during planting and after harvest. One of the pests that most often causes crops to fail during harvest time is rats. These pests usually attack communities of tens to thousands of people, causing a lot of losses. Since rat pests attack close to harvest, farmers usually drive rats out of the fields. This research method uses the R&D method. This research aims to assist farmers in repelling rat pests to get good quality rice. The test that will be used is a partial test. Where, partial tests that will be carried out on sensor parts are sensor movement tests, LoRa data transmission tests and LoRa distance measurement tests. The LoRa-based rat repellent system uses a combination of sensors and ultrasonic frequency transmitters to detect and repel rats. With LoRa (Long Range) technology, the system can send and receive data remotely with little power, which enables real-time monitoring and control of devices over a wireless network. Test results show that the system can function optimally under various environmental conditions, has a wide communication range, and responds quickly to pests. This shows that the integration of LoRa in the rat repellent system can improve pest control more efficiently and environmentally friendly than conventional methods.